Parental attitudes to children's pain and analgesic drugs in the United Kingdom. (September 2015) - Twycross, Alison M; Williams, Anna M; Bolland, Rachael E; Sunderland, Robin
Many children experience treatable moderate to severe pain following surgery. Increasingly, children undergo surgery as day cases, and, as such, parents are more likely to be responsible for managing pain post-operatively. Research in the United States and Finland has found parents fear the side effects of analgesics; think they are addictive; and that children should receive as little analgesia as possible. Little is known about parental attitudes in this context in the United Kingdom. This study set out to explore parental attitudes towards children's pain and analgesic drugs to contribute to existing knowledge about parental attitudes elsewhere so that the information provided to parents can be tailored effectively. A convenience sample of parents ( n = 108) at one hospital in South West London completed the Parental Pain Expression Perceptions and the Medication Attitudes Questionnaires. Although many parents have a good understanding of the ways in which children express pain, a substantial proportion of parents hold misconceptions regarding how children express pain and concerns in relation to analgesic drugs. This may impact on the quality of the pain management provided to children post-operatively and needs taking into account when preparing parents in this context.